Mengelola Risiko Kos-Kosan Mahasiswa dengan Pendekatan ISO 31000: Studi Kasus Sekitar Kampus Bandung - Ayesa Aulia Sofwa; Sanita Putri; Lanina Pratiwi; Siska Amelia; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study examines the implementation of ISO 31000–based risk management in boarding house businesses located in a developing suburban area in Bandung Regency. Boarding house operators commonly face risks such as delayed rental payments, facility damage, fluctuating occupancy, legal and administrative issues, and building safety concerns. Using a qualitative descriptive method and a case study approach, this research identifies, analyzes, evaluates, and treats risks according to ISO 31000 principles. The results show that the main risks include financial, operational, legal, tenant-related, and environmental safety risks. Recommended mitigation strategies include digital payment systems, routine facility maintenance, written rental agreements, improved security, and emergency procedures. Applying structured risk management enhances business continuity, service quality, and tenant trust.